Racially Disparate Expression of mTOR/ERK-1/2 Allied Proteins in Cancer - Mishra, Sanjay; Charan, Manish; Verma, Ajeet Kumar; Ramaswamy, Bhuvaneswari; Ahirwar, Dinesh Kumar; Ganju, Ramesh K. (Frontiers in Cell and Developmental Biology, 2021)
Recent studies revealed that ethnic differences in mTOR (mechanistic target of rapamycin) and ERK-1/2 (extracellular signal-regulated kinase) signaling pathways might be associated with the development and progression of different human malignancies. The African-American (AA) population has an increased rate of cancer incidence and mortality compared to the Caucasian American (CA) population. Although the socioeconomic differences across different ethnic groups contribute to the disparity in developing different cancers, recent scientific evidence indicates the association of molecular and genetic variations in racial disparities of different human malignancies. The mTOR and ERK-1/2 signaling pathways are one of the well-known oncogenic signaling mechanisms that regulate diverse molecular and phenotypic aspects of normal as well as cancer cells in response to different external or internal stimuli. To date, very few studies have been carried out to explore the significance of racial disparity with abnormal mTOR and ERK-1/2 kinase signaling pathways, which may contribute to the development of aggressive human cancers. In this review, we discuss the differential regulation of mTOR and ERK-1/2 kinase signaling pathways across different ethnic groups, especially between AA and CA populations. Notably, we observed that key signaling proteins associated with mTOR and ERK-1/2 pathway including TGF-β, Akt, and VEGFR showed racially disparate expression in cancer patients. Overall, this review article encompasses the significance of racially disparate signaling molecules related to mTOR/ERK1/2 and their potential in developing tailor-made anti-cancer therapies.